1993
DOI: 10.2134/agronj1993.00021962008500010029x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stability Analysis for Long‐Term Soil Fertility Experiments

Abstract: Long-term fertility experiments with replications are often statistically analyzed as split plots in time. Years are often shown to be significantly different and the inconsistency of treatment effects over years enters into significant year-by-treatment interactions which are difficult to interpret. The objectives of this study were to evaluate long-term fertility experiments by stability analysis and relative stability and to observe possible benefits of these analyses to complement conventional analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 11 publications
0
60
2
1
Order By: Relevance
“…They found that compared with NPK, the combined application of NPK and FYM resulted in a higher increase in SOC in the maize and wheat-maize systems than in rice and rice-wheat systems, and in increased crop yields during the last few years of the experiment for the maize and wheat-maize systems, but during the initial years in the rice and rice-wheat systems. Zhang et al (2009c) found that longterm application of pig manure resulted in continuous increase in SOC and total soil N in a wheat-corn rotation system, and that the highest rate of NPKM increased SOC the most, while the application of only inorganic fertilizers had little influence on SOC, but decreased total soil N. Raun et al (1993) found that when environmental conditions were not good (environmental mean yield was <2 Mg ha −1 ), the NPK-treated plots had better yield than the cattle manure treatment, while when the growing conditions were optimal, cattle manure treatment had a better performance. Thus, the combination of both types of fertilizers produced a more stable yield.…”
Section: Combination Of Inorganic and Organic Fertilizers Leads To Momentioning
confidence: 99%
“…They found that compared with NPK, the combined application of NPK and FYM resulted in a higher increase in SOC in the maize and wheat-maize systems than in rice and rice-wheat systems, and in increased crop yields during the last few years of the experiment for the maize and wheat-maize systems, but during the initial years in the rice and rice-wheat systems. Zhang et al (2009c) found that longterm application of pig manure resulted in continuous increase in SOC and total soil N in a wheat-corn rotation system, and that the highest rate of NPKM increased SOC the most, while the application of only inorganic fertilizers had little influence on SOC, but decreased total soil N. Raun et al (1993) found that when environmental conditions were not good (environmental mean yield was <2 Mg ha −1 ), the NPK-treated plots had better yield than the cattle manure treatment, while when the growing conditions were optimal, cattle manure treatment had a better performance. Thus, the combination of both types of fertilizers produced a more stable yield.…”
Section: Combination Of Inorganic and Organic Fertilizers Leads To Momentioning
confidence: 99%
“…Although the effect of manure application on yield is lower than that of NPK fertilization, usage of farmyard manure brings about other positive aspects, especially to soil properties. It serves, for instance as a source of organic matter, it increases stability of soil aggregates, influences soil water regime, activity of soil microorganisms and amount of microbial biomass (Raun et al 1993, Karlen and Doran 1993. A greater effect on grain yield of cereals is reported at combined application of manure and mineral fertilizers (Manna et al 2005).…”
Section: Treatmentmentioning
confidence: 99%
“…Practically, longterm experiments enable observations on changes in crop growth patterns and management effects on slow-moving factors such soil organic matter, which cannot be done in any other way (Jenkinson 1991;Mitchell et al 1991). They are important for designing cropping systems with high and stable crop yields and low production risk (Raun et al 1993;Stanger et al 2008). We analysed maize grain yield data from rain-fed long-term studies on tillage and residue management from semi-arid to sub-humid environments.…”
Section: Introductionmentioning
confidence: 99%